Is it all about CO2 emissions? The environmental effects of a tax reform for new vehicles in Norway - Alice Ciccone (University of Oslo, Department of Economics, 2014)
In 2007, the Norwegian government reformed the vehicle registration tax in order to reduce the CO2 emissions intensity of the new car fleet by incentivizing the purchase of more fuel efficient cars. This paper identifies the impact of the new tax structure on four dimensions: 1) the average CO2 emissions intensity of new registered vehicles, 2) the relative change between low and high polluting cars, 3) the market share of diesel cars and 4) the average weight of the fleet. A Difference in Difference approach is employed to estimate the short run effects on each outcome variable of interest. The results show that, as a consequence of the tax reform, the average CO2 intensity of new vehicles was reduced in the short run by at least 6 gCO2/Km, which is about half of the overall reduction observed when including supply effects. This reduction is the result of a 12 percentage points drop in the share of highly polluting cars and of an increase of about 23 percentage points in the market share of diesel cars. Lastly, the mass of the average fleet increased by at least 10 Kg.
Keywords: H25; L62; Q51; Q53; Q54; Q58; R48; 330; CO2 emissions intensity; New vehicles; Vehicle registration tax; Tax reform; Norway; Diesel